2020
DOI: 10.1093/tas/txaa031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Megasphaera elsdenii and feeding strategies on feedlot performance, compositional growth, and carcass parameters of early weaned, beef calves

Abstract: Simmental–Angus calves [n = 135; 72 steers and 63 heifers; body weight (BW) = 212.4 kg ± 36.1] were early weaned (~5 mo) to evaluate multiple feeding regimens (conventional vs. aggressive energy diets ± Megasphaera elsdenii NCIMB 41125 (M. elsdenii culture (MEC); Lactipro Advance; MS Biotec Inc., Wamego, KS) in order to elucidate the optimal development strategy. Objectives were measured by tracking the effects of caloric density and oral drenching of growing phase performance and subsequent carcass traits. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
2
8
1
1
Order By: Relevance
“…The lack of statistical significance on mean DMI for animals dosed with MEG corroborate with other studies in beef ( Drouillard et al, 2012 ; DeClerck et al, 2020a ; DeClerck et al, 2020b ; DeClerck et al, 2020c ) and dairy cattle ( Aikman et al, 2011 ; Henning et al, 2011 ). Evaluating a subacute ruminal acidosis ( SARA ) model, Mazon et al (2020) demonstrated that MEG administration 4 d prior to the challenge reduced the time-period and area at which rumen pH remained below 5.8 and 5.6, as well as improved DMI and milk production of mid-lactation dairy animals.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The lack of statistical significance on mean DMI for animals dosed with MEG corroborate with other studies in beef ( Drouillard et al, 2012 ; DeClerck et al, 2020a ; DeClerck et al, 2020b ; DeClerck et al, 2020c ) and dairy cattle ( Aikman et al, 2011 ; Henning et al, 2011 ). Evaluating a subacute ruminal acidosis ( SARA ) model, Mazon et al (2020) demonstrated that MEG administration 4 d prior to the challenge reduced the time-period and area at which rumen pH remained below 5.8 and 5.6, as well as improved DMI and milk production of mid-lactation dairy animals.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, the lack of ruminal disorders in MEG-0 and MEG-6 supports the efficacy of MEG in alleviating the occurrence of digestive disorders in beef cattle offered a high-concentrate diet without a step-up adaptation period ( Kettunen et al, 2008 ; Horn et al, 2009 ; McDaniel et al, 2009 ; DeClerck et al, 2020b ). DeClerk et al (2020c) also did not report any case of clinical acidosis in beef calves abruptly transitioned from a grower to a finishing diet over a short period of time, supporting the efficacy and success of ruminal colonization after exogenous MEG drench. Removing the adaptation diet from the feedlot might benefit the entire operation, given the elevated cost per unit of energy and that the use of forage and consequent the space required to store this bulky material will consequently decrease ( Buttrey et al, 2012 ; Schneider et al, 2017 ).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations